Inovasi IPTEK dan Peningkatan Mutu Pelayanan Sebagai Langkah Pengambilan Kebijakan Pemerintah Daerah di Kabupaten Brebes - Susanto, Agus Redi (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Brebes, 2023)
Science and technology is a solution that must be planned and implemented in order to be competitive for developing countries because they have the ability to innovate to become a strong, independent, respected country and produce quality human resources for the common good of the people. In this technology, the system plays an important role in creating innovation, especially in the field of science and technology, as well as in quality management of public services. Over time, globalization and rapid technological revolutions have developed, which pose very serious challenges to current governments and global and regional developments, affecting the social life of people and countries modern, competent and honest public service quality. Implementing a globally competitive government requires analysis, productivity assessment, service quality improvement, as well as comprehensive, integrated, open and high quality science and technology policy planning and innovation.